The Paradox of Freedom of Expression: An Evaluation of the Implementation of the ITE Law from a Human Rights Perspective in Indonesia - Amelia Puspita; Melyana (Ekasakti Journal of Law and Justice, 2026)
This study aims to analyze the impact of the implementation of ambiguous provisions in the Electronic Information and Transactions Law (EIT Law) on freedom of expression, and to evaluate them based on human rights principles. The research method employed is a normative legal approach, with data collected through a literature review of secondary sources. The results of the study indicate that the existence of “vague” provisions such as Articles 27, 28, and 29 of the EITL creates legal uncertainty and triggers a chilling effect in society. Inconsistent law enforcement that frequently disregards the principle of due process of law leads to the criminalization of public criticism, which contradicts the international standards of the ICCPR. The conclusion of this study emphasizes the need for regulatory reform through the reconstruction of norms in accordance with the principle of lex certa and the prioritization of the ultimum remedium approach. The transformation of digital law must be able to integrate human rights values to ensure a balance between public stability and the protection of democratic aspirations.